2017
DOI: 10.1371/journal.pone.0177933
|View full text |Cite
|
Sign up to set email alerts
|

Production of transgenic pig as an Alzheimer’s disease model using a multi-cistronic vector system

Abstract: Alzheimer’s disease (AD) is a progressive neurodegenerative disease associated with memory loss and cognitive impairments. An AD transgenic (Tg) pig model would be useful for preclinical testing of therapeutic agents. We generated an AD Tg pig by somatic cell nuclear transfer (SCNT) using a multi-cistronic vector that harbored three AD-related genes with a total of six well-characterized mutations: hAPP (K670N/M671L, I716V, and V717I), hTau (P301L), and hPS1 (M146V and L286P). Four AD Tg cell lines were establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…In turn, another group obtained AD transgenic pigs using a retroviral multi-cistronic vector containing three AD-related human genes: APP, Tau, and PSEN1, with a total of six well-characterized mutations under the control of a fusion promoter: CMVE+ hPDGFβ promoter region. They confirmed that transgenes were expressed at high levels in brain tissue and demonstrated a two-fold increase in Aβ levels in the brains of transgenic pigs compared to wild-type [29].…”
Section: Alzheimer's Diseasementioning
confidence: 60%
“…In turn, another group obtained AD transgenic pigs using a retroviral multi-cistronic vector containing three AD-related human genes: APP, Tau, and PSEN1, with a total of six well-characterized mutations under the control of a fusion promoter: CMVE+ hPDGFβ promoter region. They confirmed that transgenes were expressed at high levels in brain tissue and demonstrated a two-fold increase in Aβ levels in the brains of transgenic pigs compared to wild-type [29].…”
Section: Alzheimer's Diseasementioning
confidence: 60%
“…Still, when four 8-year-old and a single 14-year-old sheep were analyzed, Tau tangle-like structures were identified in 3 of the four 8-year-old sheep, and Aβ-immunopositive plaques were identified in all animals, although most plaques were diffuse 34 . AD transgenic pigs have recently been generated 53 , but the thickness of the pig skull continues to increase with aging 54 , making this species less suitable for aged, AD, or longitudinal studies. Minipigs also possess large, air-filled sinuses atop the skull, which would block ultrasound transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pigs, especially minipigs, also share a number of similarities with human, such as body size, anatomy, physiology, pathology as well as genome, providing an excellent animal model for mimicking human diseases (Nagashima et al, ; Niemann & Lucas‐Hahn, ; Prather et al, ; Whyte & Prather, ). Genetically modified pigs have also been widely used for modelling numerous human diseases, such as Alzheimer’s disease (Kragh et al, ; Lee et al, ), Huntington’s disease (Yan et al, ; Yang et al, ) and Parkinson’s disease (Wang et al, ; Zhou et al, ). Therefore, genetically modified pigs hold great promise in the fields of agriculture and biomedicine.…”
Section: Discussionmentioning
confidence: 99%